RELATION BETWEEN PARASITES AND BASIC SANITATION. - Busato, Maria Assunta; Antoniolli, Marinez Amabile; Paz Arruda Teo, Carla Rosane; Ferraz, Lucimare; Poli, Gianfranco; Tonini, Paulo (Ciencia, Cuidado e Saude)
Parasites affect different ages, parasite and environment characteristics are key to parasite installation in hosts. The aim of this study was to relate intestinal parasites prevalence in Brazilian public health system patients and sanitation condition. 1004 exams of fecal parasitological were analyzed in the City Clinical and Environmental Analysis Laboratory. Basic sanitation data was obtained from Information System of Basic Care. The quantitative analysis was performed with Excel and Statistical Package for the Social Sciences programs. Parasites prevalence found was 12.5% with 10.3% polyparasitism and greater contamination risk at 7.5 years old. Entamoeba coli (28.4%), Endolimax nana (24.8%) and Giardia lamblia (18.9%) were the most frequently observed. The least prevalence and risk to parasites in Family Health Centers had also best basic sanitation. Parasites positivity includes all ages, parasite contamination biggest risk at 7.5 years old. Within the study region the basic sanitation, make evident relation to parasites presence.